Jerozolima czasów Sedecjasza jako arena działalności proroka Jeremiasza - Malkusz, Sebastian (Scriptura Sacra, 2018)
Information about the time horizon of the prophet Jeremiah’s activities can be already found in the first three lines of the book. According to these data, servant of the word from Anathoth conducted his prophetic activities during the reign of three successive rulers of Judah: Josiah, Jehoiakim and Zedekiah. The subject of this article is historical-archaeological background for the prophet’s appearances in Jerusalem, during the Zedekiah times. This king was not, however, a great builder and shape of the city was developed by his predecessors. The first paragraph is therefore a historical-archaeological outline of the city prior to Zedekiah’s reign. The second paragraph provides an analysis of the rule of the king and his advisors, as well as the spiritual and moral condition of the inhabitants of the holy city. The third section introduces the places of Jerusalem mentioned in the book of Jeremiah. In the fourth paragraph, one can find texts of Jeremiah’s book that refer to the time of Zedekiah.